Multi-Channel Method of Non-isolated DC Voltmeter for EFI Instrument Measure. (December 2020) - Adiyasa, I W; Solikin, M; Khalid, H; Umar, A; Riyan, I N
Abstract: The use of instruments for vehicle repair is very important to use. However, the instrument is very expensive and many features are not used. So that in this study designed a simple measuring instrument that is able to measure the size of the sensor. The tool uses a 32bit based microcontroller integrated with bluetooth. There are 4 voltage gauge channels. The reading data is communicated to the graphic user interface (GUI) on the laptop device. The measuring instrument can record the measured sensor on a vehicle for 1 minute for analysis.